2013
DOI: 10.1038/onc.2013.186
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 3 promotes cancer cell migration and invasion by regulating activator protein 1 and protein kinase C-dependent-Ezrin activation

Abstract: Desmoglein 3 (Dsg3), the pemphigus vulgaris antigen, has recently been shown to be upregulated in squamous cell carcinoma (SCC) and has been identified as a good tumor-specific marker for clinical staging of cervical sentinel lymph nodes in head and neck SCC. However, little is known about its biological function in cancer. The actin-binding protein Ezrin and the activator protein 1 (AP-1) transcription factor are implicated in cancer progression and metastasis. Here, we report that Dsg3 regulates the activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 79 publications
8
70
0
Order By: Relevance
“…Overexpression of Dsg3 in the oral squamous cell carcinoma (OSCC) cell lines A431 and SqCC/Y1 caused a marked increase in phosphorylation of the conserved ezrin residue T567, which resulted in increased migration and invasion in 3D cell culture assays. It has been suggested that ezrin is phosphorylated by PKC after its colocalisation with Dsg3, an interaction that might be responsible for the metastatic potential of OSCC cell lines (Brown et al, 2013). Ezrin has previously been proposed to act as a downstream signalling molecule in PKCinduced cell migration; here, PKCa phosphorylates specifically the conserved T567 residue on ezrin (Ng et al, 2001), which results in CD44-dependent directional migration (Legg et al, 2002).…”
Section: Ezrinmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of Dsg3 in the oral squamous cell carcinoma (OSCC) cell lines A431 and SqCC/Y1 caused a marked increase in phosphorylation of the conserved ezrin residue T567, which resulted in increased migration and invasion in 3D cell culture assays. It has been suggested that ezrin is phosphorylated by PKC after its colocalisation with Dsg3, an interaction that might be responsible for the metastatic potential of OSCC cell lines (Brown et al, 2013). Ezrin has previously been proposed to act as a downstream signalling molecule in PKCinduced cell migration; here, PKCa phosphorylates specifically the conserved T567 residue on ezrin (Ng et al, 2001), which results in CD44-dependent directional migration (Legg et al, 2002).…”
Section: Ezrinmentioning
confidence: 99%
“…A so far unknown interaction between ezrin and the desomosome protein desmoglein 3 (Dsg3) has recently been identified; and Dsg3 appears to colocalise with ezrin at the plasma membrane (Brown et al, 2013). Overexpression of Dsg3 in the oral squamous cell carcinoma (OSCC) cell lines A431 and SqCC/Y1 caused a marked increase in phosphorylation of the conserved ezrin residue T567, which resulted in increased migration and invasion in 3D cell culture assays.…”
Section: Ezrinmentioning
confidence: 99%
“…This suggests that other proteins may also be involved. Other cadherins, such as Nand P-cadherin and other desmosomal adhesion proteins (such as DSG1, DSG3, DSG4, DSC1 and DSC3), might take part in this process as their activities are associated with cancer development (1,6,22,30,40). Their involvement requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between these two superimposed mechanisms does not need to be strictly causal. Podoplanin does not necessarily alter the effective cohesiveness at the beginning of the process (Brown et al, 2014;de Toledo et al, 2012;Ewald et al, 2012;Hartsock and Nelson, 2012;Priya et al, 2013;Ratheesh et al, 2013;Smith et al, 2012). Gotzmann et al (2004) have proposed a two-hit model for epithelial cell plasticity, so that a given cell line could be "pre-activated" and need only one signal or two signals to trigger EMT; for example, TGF-β and active Ras, or TGF-β and EGF.…”
Section: Role Of Podoplanin In Emtmentioning
confidence: 99%